Notary According To Civil Law And Common Law That Related Strongly With International Civil Transactions - Ma - Junyu (Jurnal Akta, 2020)
The world is increasingly without borders which has an impact on legal services such as the world of civilization, especially notary. However, in reality there are still many intersections of legal systems that are increasingly widespread in the notary world that are included in civil law, for example, the practice of international trade has made the boundaries between legal systems increasingly thin. Including differences in the use of legal systems such as Civil Law and Common Law in each country also affects the development and type of civil law system. For example, the bookkeeping and business taxation system will be built based on certain legal systems across jurisdictional boundaries including land lease agreements for industries with foreign investors.